Liquid-phase exfoliated fluorographene as a two dimensional coating filler for enhanced corrosion protection performance. (February 2016) - Yang, Zhengqing; Sun, Wen; Wang, Lida; Li, Sijia; Zhu, Tianzhen; Liu, Guichang
Abstract: Though a promising corrosion protection material, graphene can accelerate metal corrosion due to its thermodynamic stability and high conductivity. In this work, few-layer fluorographene (FG) is prepared by a liquid-phase exfoliation method and incorporated into polyvinyl butyral (PVB) coating to enhance its corrosion protection performances. The results show that the introduced FG confers enhanced barrier property on the PVB coating by preventing the penetration of aggressive species. Besides, unlike graphene, FG cannot promote metal corrosion because the insulating nature of FG impedes the formation of metal-filler galvanic corrosion cell.